Art, entertainment and politics: Alessandro Blasetti and the rise of the Italian film industry, 1929–1959. Issue 1 (2nd January 2020) - Gundle, Stephen; Zegna, Michela
Abstract : This article explores the role of Alessandro Blasetti in arguing for, and promoting, the development of the Italian film industry before and after the Second World War. Though a prominent film director for more than thirty years, Blasetti was never considered an auteur: he had no distinct authorial style and not did he specialise in any particular genre. Unlike some postwar directors, he never positioned himself in opposition to producers but, on the contrary, worked closely with many of them, winning a reputation for reliability and professionalism. A supporter of Fascism until the later 1930s, he encouraged state involvement in the industry and was the first to use the Cinecittà studios, inaugurated in 1937, to their full potential. After the war, he mediated between opposing political forces to defend the interests of the Italian cinema as an industry and a 'collective art'. He was responsible for creating several stars, including Gino Cervi and Sophia Loren. Drawing on the Blasetti archive, the article considers the range of the director's activities, political links and his way of conceiving his role, immersed in rather than against the industry.